Analysis of the Structure-Function-Dynamics Relationship of G-Protein Coupled Receptors - Olthafer, Augustus J. (My University, 2014)
The presence of G-proteins and G-protein coupled receptors (GCPRs) are highly ubiquitous in upper eukaryotic organisms. With nearly 60% of all modern pharmaceuticals targeting GCPRs, the understanding of these proteins' dynamical-functional-structural relationship is critical for designing better drug molecules. A wide variety of GCPR proteins exist, differing by the ligands they bind, their cellular responsive mechanisms and their intrinsic properties. The purpose of this study was to examine the role of GPCRs' active site dynamics in recognizing and binding the appropriate ligand and how these intrinsic dynamics differ between different classes of GPCRs.
Color poster with text, charts, images, tables, and graphs.
Keywords: G-protein coupled receptors (GCPRs); Ligands; Posters